Incidence of seizures following initial ischemic stroke in a community-based cohort: The Framingham Heart Study - Stefanidou, Maria; Das, Rohit R.; Beiser, Alexa S.; Sundar, Banu; Kelly-Hayes, Margaret; Kase, Carlos S.; Devinsky, Orrin; Seshadri, Sudha; Friedman, Daniel (Seizure (London, England), 2017)
•The incidence of seizures following an ischemic stroke is 5%.•The majority of post-stroke seizures occur within the first 24h after a stroke.•Lower rates of seizure-free survival are seen with higher disability after stroke. We examined the incidence of seizures following ischemic stroke in a community-based sample. All subjects with incident ischemic strokes in the Framingham Original and Offspring cohorts between 1982 and 2003 were identified and followed for up to 20 years to determine incidence of seizures. Seizure-type was based on the 2010 International League Against Epilepsy (ILAE) classification. Disability was stratified into mild/none, moderate and severe, based on post-stroke neurological deficit documentation according to the Framingham Heart Study (FHS) protocol and functional status was determined using the Barthel Index. An initial ischemic stroke occurred in 469 subjects in the cohort and seizures occurred in 25 (5.3%) of these subjects. Seizure incidence was similar in both large artery atherosclerosis (LAA) (6.8%) and cardio-embolic (CE) (6.2%) strokes. No seizures occurred following lacunar strokes. The predominant seizure type was focal seizure with or without evolution to bilateral convulsive seizure. One third of participants had seizures within the first 24h from stroke onset and half of all seizures occurred within the first 30days. On multivariate analysis, moderate and severe disability following stroke was associated with increased risk of incident seizure. Seizures occurred in approximately 5% of subjects after an ischemic stroke. One third of these seizures occurred in the first 24h after stroke and none followed lacunar strokes. Focal seizures with or without evolution in bilateral convulsive seizures were the most common seizure type. Moderate and severe disability was predictive of incident seizures.